From The Wire to Swedish Socio-Crime: Police Procedural and Social Criticism - Tomić, Janica (2010)
After compiling a generic description of police procedural and the devices commonly ascribed to that sub-genre in comparison with other crime fiction, the following analysis discusses how the HBO's show The Wire shifts from the conventions of both police procedural and the crime genre’s syntax in general. The last section of the paper draws comparisons with examples of a distinct Swedish tradition of police procedurals that have long been recognized as "the sozio-krimi".
Projekt MZOS
ENG